OsGLP participates in the regulation of lignin synthesis and deposition in rice against copper and cadmium toxicity - ShangGuan, Xiangchao; Qi, Ying; Wang, Aiguo; Ren, Yingnan; Wang, Yu; Xiao, Tengwei; Shen, Zhenguo; Wang, Qi; Xia, Yan (Frontiers in Plant Science, 2023)
Copper (Cu) and cadmium (Cd) are common heavy metal pollutants. When Cd and excessive Cu accumulate in plants, plant growth is reduced. Our previous study showed that Germin-like proteins (GLPs), which exist in tandem on chromosomes, are a class of soluble glycoproteins that respond to Cu stress. In this study, knockout of a single OsGLP8-2 gene or ten OsGLP genes (OsGLP8-2 to OsGLP8-11) resulted in a similar sensitivity to Cd and Cu toxicity. When subjected to Cu and Cd stress, the glp8-2 and glp8-(2-11) mutants displayed a more sensitive phenotype based on the plant height, root length, and dry biomass of the rice seedlings. Correspondingly, Cu and Cd concentrations in the glp8-2 and glp8-(2-11) mutants were significantly higher than those in the wild-type (WT) and OsGLP8-2-overexpressing line. However, Cu and Cd accumulation in the cell wall was the opposite. Furthermore, we determined lignin accumulation. The overexpressing-OsGLP8-2 line had a higher lignin accumulation in the shoot and root cell walls than those of the WT, glp8-2, and glp8-(2-11). The expression of lignin synthesis genes in the OsGLP8-2-overexpressing line was significantly higher than that in the WT, glp8-2, and glp8-(2-11). The SOD activity of OsGLP8-2, Diaminobe-nzidine (DAB), propidium iodide (PI) staining, and Malondialdehyde (MDA) content determination suggested that OsGLP8-2 is involved in heavy metal-induced antioxidant defences in rice. Our findings clearly suggest that OsGLPs participate in responses to heavy metal stress by lignin deposition and antioxidant defence capacity in rice, and OsGLP8-2 may play a major role in the tandem repeat gene clusters of chromosome 8 under heavy metal stress conditions.